An evaluative case study of curriculum development and implementation in PELUM College - Mukute, Mutizwa (Rhodes University, Faculty of Education, Department of Education, 2001)
This evaluative study examined the development and implementation of a multi-disciplinary agroecology and community development curriculum by PELUM College Zimbabwe, The college, which emerged to implement the curriculum, comprises of non-govemmental organisations, university departments and government agencies coordinated by PELUM Association, PELUM supports participalory ecological land-use management and the curriculum was aimed at community development workers, The curriculum's four pillars were: community development facilitation; natural resources management; sustainable crop and animal production; and organisational management. The study explored the conceptual integrity of the socially-critical oriented curriculum, focusing on the written curriculum; resource material development; participation; praxis; assessment and accreditation; as well as project planning and implementation by trainees, The methodology was essentially interpretive, with a participatory and praxiological orientation inspired by the socially critical framework of the curriculum, I gathered data over two years, analysing documents covering a period of nine years, and involving about 75 participants in the research through questionnaires, in-depth semi-slructured interviews and focus group discussions, My key findings were that the curriculum and the participatory process in which it had been developed and implemented had potential to address pedagogical and developmental shortcomings of more conventional curricula, The major weaknesses in the curriculum and its development arose from the under-utilisation of the curriculum framework that should have guided participation and decision-making, I examined tensions in the curriculum implementation, finding them similar to those experienced in other environmental education programmes in the reg ion, In keeping with the praxiological and formative orientation to the evaluation, I conclude with recommendations specific to the case under study,
Keywords: Curriculum planning; PELUM College (Zimbabwe); Curriculum planning -- Zimbabwe